Value network orchestration of a cognitive radio platform - Ankit Taparia; Arturo Basaure; Thomas R. Casey (International Telecommunications Society (ITS), 2012)
Mobile communication industry has taken over path of platformisation in terms of service provisioning leading to emergence of different platforms. These service oriented platforms have opened up otherwise closed and vertically integrated mobile industry. However in terms of spectrum licensing and usage market structure is still relatively closed and cognitive radio (CR) technology is expected to be at forefront to solve these issues. With development of CR technologies new stakeholders are expected to emerge and join existing market players resulting in the development of a multi-sided platform. In this paper we introduce spectrum database driven CR platform as an integral part of CR ecosystem. We visualize its architecture in form of set of layered and interconnected platforms. Higher layer platform for services catering to end-users, lower layer platform for different CR access technologies and a generic CR protocol in between binding these layered platforms. In order to understand how to orchestrate the value network for different stakeholders to participate in this CR platform, we conducted interviews and identified that stakeholders are in principle willing to move out of their silos and think holistically in terms of CR platform. However political uncertainties and regulatory indecision happens to be major cause of concern hampering stakeholders to make required investments. Also observed that regulators are in position to orchestrate CR market place since their actions influence market, market participants and technology. Thus regulators are required to take steps in direction which promotes harmonization of CR technologies and prevent a fragmented scenario where none of CR solutions attain required critical mass.
Keywords: 330